5*(x-3)+7=

Simple and best practice solution for 5*(x-3)+7= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5*(x-3)+7= equation:


Simplifying
5(x + -3) + 7 = 0

Reorder the terms:
5(-3 + x) + 7 = 0
(-3 * 5 + x * 5) + 7 = 0
(-15 + 5x) + 7 = 0

Reorder the terms:
-15 + 7 + 5x = 0

Combine like terms: -15 + 7 = -8
-8 + 5x = 0

Solving
-8 + 5x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '8' to each side of the equation.
-8 + 8 + 5x = 0 + 8

Combine like terms: -8 + 8 = 0
0 + 5x = 0 + 8
5x = 0 + 8

Combine like terms: 0 + 8 = 8
5x = 8

Divide each side by '5'.
x = 1.6

Simplifying
x = 1.6

See similar equations:

| -20m=220 | | 4t^2-2t-8=0 | | 6t-t-3=4t-5 | | 2n+1=-98 | | x^2-13x+120=0 | | -(4xy-9)+2(3xy+4)= | | 3x+x-7=3x+3 | | 3-5/2x/5x+7/4x^2 | | 12x-7+4x=5x+3x-7 | | 3n-1-(n-4)-[2(n-3)-3(1-2n)]=-n-2 | | 3/5w+9=-1 | | x+x+4+x+4=44 | | 2g^2+9g+7=0 | | (x-3)^2/5=4 | | -3(7p+3)-2(1-14p)=3(1+2p) | | 5x-3x-7=28 | | 2x+17=2y+10 | | 4(x-12)=5(x-15) | | 4x+14=-12-7x | | 5.4*(x-3)= | | 3(a-4)+5(a-2)=2(a-6)-4(5-a) | | 6(3z+1)-z-22= | | A+(a+1)=96 | | t^2+6t-35=0 | | ax-c=bx+5c | | -12-24d=3(a-15) | | 6x-25=x+34 | | 39=-2x+7x-1 | | 15x^2-17xy-4y^2=0 | | (m+7)*3=(m-3)*4 | | -16+a=-14 | | 3(z-1)-4(5-z)=2(6+z) |

Equations solver categories